Assessing the impact of fiscal freedom and the rule of law upon output growth in some Central and Eastern European countries - Blikhar, Mariia; Sokurenko, Solomiya; Hodiak, Andrii; Ilkiv, Yuliia; Kashchuk, Mariana; Kucher, Anatolii (Technology audit and production reserves, 2025)
The object of the study was selected to be several countries of Central and Eastern Europe (Poland, Romania, the Czech Republic, Hungary) and Ukraine, where one of the problem areas is the dependence of economic growth on fiscal freedom and the rule of law. To study this functional relationship, it is possible to use empirical estimates for quarterly data from 2010 to 2022 using the GMM method. The empirical estimates obtained for individual countries show significant differences in the impact of fiscal freedom and the rule of law on income. This allows to better understand the specifics of fiscal policy and institutional transformation in the selected countries. There are several main results. First, improving the financial situation is favorable for economic growth in Poland, Romania, and Ukraine, but unfavorable in the Czech Republic (there is no effect in Hungary). Second, it was found that lower government spending is beneficial for economic growth only in Romania and Hungary (to a lesser extent). At the same time, for the Czech Republic and Ukraine, an increase in government spending is preferable. Third, the protection of property rights encourages economic growth only in Ukraine. The inverse relationship for Central and Eastern European countries may mean that administrative guarantees in the area of property rights are much stricter than the achieved income level would suggest. Fourth, the efficiency of the judicial system is found to encourage economic growth in 4 out of 5 countries except the Czech Republic. The paper confirms the findings of other studies for Central and Eastern European countries and Ukraine that currency devaluation in nominal and real terms hinders economic growth. Money emission and interest rate increases in the US are favorable for economic growth in all countries. The consequences for economic growth of the increase in global crude oil prices, the COVID-19 pandemic and the period of extremely low interest rates (ZLB) in 2010–2020 differ across countries.